Literacy on the Unified Global Hijri Calendar and Basic Hisab Training at a Muhammadiyah Islamic Boarding School - Alamsyah Alamsyah; St. Muthaharah; Abdillah S; Hisbullah Salam; Erty Rospyana Rufaidah (Khidmatuna : Jurnal Pengabdian Masyarakat, 2026)
This community engagement program aimed to strengthen literacy on the Unified Global Hijri Calendar (Kalender Hijriah Global Tunggal, KHGT) and basic operational hisab skills among members of a Muhammadiyah Islamic boarding school community in Makassar. The program was designed in response to the partner community’s need to understand the fiqh foundations, the Muhammadiyah tarjih methodology, astronomical arguments, and the practical use of official calendar information in religious and institutional life. The engagement employed Participatory Action Research (PAR) combined with a service-learning orientation through four phases: joint needs diagnosis, collaborative program planning, KHGT literacy and basic hisab training, and reflection-evaluation for follow-up planning. Thirty participants took part in the activity, consisting of students, teachers/ ustaz, mentors, and members of the pesantren community. Data were collected through participatory observation, documentation, participant feedback, and pre-test and post-test instruments based on KHGT literacy indicators. The results indicate a substantial descriptive improvement. The participants’ mean score increased from 49.3 in the pre-test to 89.3 in the post-test, representing a 40-point increase and an N-gain of 0.79, which falls into the high category. All participants obtained a minimum post-test score of 75, and 73.3% achieved scores of 85 or higher. Beyond cognitive improvement, the program generated direct outputs for the partner institution, including KHGT literacy materials, worksheets for practicing calendar interpretation, and an internal cadre-development plan. These findings suggest that pesantren-based KHGT literacy can serve as a community capacity-building strategy that enables religious communities to understand the global Islamic calendar in a scientific, sharia-based, practical, and sustainable manner.